1996
DOI: 10.1109/9.543999
|View full text |Cite
|
Sign up to set email alerts
|

Stability conditions for multiclass fluid queueing networks

Abstract: We find necessary and sufficient conditions for the stability of all work-conserving policies for multiclass fluid queueing networks with two stations. Furthermore, we find new sufficient conditions for the stability of multiclass queueing networks involving any number of stations and conjecture that these conditions are also necessary. Previous research had identified sufficient conditions through the use of a particular class (monotone piecewise linear convex) potential functions. We show that for two-statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…In these unstable examples, the total number of jobs in the system goes to inÿnity with time. Other recent work on the stability of queueing networks and uid networks includes Harrison and Nguyen (1995), Bramson (1997Bramson ( , 1999, Bertsimas et al (1996), Dumas (1996Dumas ( , 1997, Dai and Weiss (1996), Foss and Rybko (1995), Winograd and Kumar (1996), , Chen andZhang (1997, 1998), Morrison and Kumar (1998), and Hasenbein (1997).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these unstable examples, the total number of jobs in the system goes to inÿnity with time. Other recent work on the stability of queueing networks and uid networks includes Harrison and Nguyen (1995), Bramson (1997Bramson ( , 1999, Bertsimas et al (1996), Dumas (1996Dumas ( , 1997, Dai and Weiss (1996), Foss and Rybko (1995), Winograd and Kumar (1996), , Chen andZhang (1997, 1998), Morrison and Kumar (1998), and Hasenbein (1997).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bertsimas et al (1996) showed that a twostation uid network is globally stable if and only if a certain linear program has bounded objective value. In this paper we extend the results of Bertsimas et al by stating explicitly, in terms of the arrival rates and service times, necessary and su cient conditions for a two-station uid network to be globally stable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inequality (19) is a Lyapunov drift condition of the form developed in [41,18], and also similar to the bounds used in [11,4,28,26,43] to obtain performance bounds for networks. Under natural assumptions on the model the bound (19) implies that the controlled network is geometrically ergodic, so that the mean E[c(Q(t))] converges to its steady-state value geometrically fast from each initial condition [41,42,40,26,36,19].…”
Section: Work-stoppage Under a Myopic Policymentioning
confidence: 99%
“…(ii) Optimized solutions for problems formulated on the fluid model can lead to efficient solutions for the corresponding problems formulated on the original stochastic network [8,9,10,11]. On the other hand, many of the flow control problems defined in the context of the abstracting fluid networks can be quite challenging themselves, giving rise to some very interesting optimal control problems [12,13]. The recent publication of [14] offers an excellent treatment of the role of fluid models in the control of complex stochastic networks, and it defines the state-of-art in this area.…”
mentioning
confidence: 99%